1999
DOI: 10.1086/314605
|View full text |Cite
|
Sign up to set email alerts
|

Peroral Famciclovir in the Treatment of Experimental Ultraviolet Radiation–Induced Herpes Simplex Labialis: A Double‐Blind, Dose‐Ranging, Placebo‐Controlled, Multicenter Trial

Abstract: Three doses of famciclovir were tested for treatment of experimental ultraviolet radiation (UVR)-induced herpes labialis. Patients received 125, 250, or 500 mg of famciclovir or placebo 3 times a day for 5 days beginning 48 h after UVR exposure, a model of early episodic intervention. Of 248 patients irradiated, 102 developed lesions while on treatment. There were no significant differences between groups in the number of lesions. The mean maximal lesion size was reduced in a dose-proportional manner: 139, 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 36 publications
2
43
0
1
Order By: Relevance
“…The lips of the patients were exposed to UVR (study day 0) within 7 days of the initial reading. The half of the lips (either the lower lip, the upper lip, or the right or left portions of both the lower and upper lips) that was regarded as the usual site of recurrence was exposed to UVR as described above for a duration four times the MED, as described previously (3,8,11). The remainder of the lips and the perioral skin outside this zone were covered with a para-aminobenzoic acidcontaining sunscreen with a sun protection factor of at least 30.…”
Section: Study Medicationmentioning
confidence: 99%
“…The lips of the patients were exposed to UVR (study day 0) within 7 days of the initial reading. The half of the lips (either the lower lip, the upper lip, or the right or left portions of both the lower and upper lips) that was regarded as the usual site of recurrence was exposed to UVR as described above for a duration four times the MED, as described previously (3,8,11). The remainder of the lips and the perioral skin outside this zone were covered with a para-aminobenzoic acidcontaining sunscreen with a sun protection factor of at least 30.…”
Section: Study Medicationmentioning
confidence: 99%
“…Clinical trials have shown that FCV is effective in the treatment of acute herpes labialis and genital herpes (39,41) and as a prophylactic treatment of UV-induced herpes labialis, excimer laser skin resurfacing, and genital herpes (2,11,43,44). We report that FCV may be beneficial in reducing corneal morbidity in patients with recurrent herpes keratitis.…”
Section: Vol 45 2001 Fcv Effect On Hsv Corneal Disease and Latencymentioning
confidence: 80%
“…FCV is currently approved for the treatment of herpes zoster and the treatment and suppression of genital herpes (7,9). FCV has also been used in clinical trials for herpes labialis (2,8,11,39,41,43,44). A clinical trial by Spruance et al (44) demonstrated that oral FCV decreased the median lesion size in a dose-dependent manner and that, at higher doses, it decreased the time to healing following UV radiation-induced HSV labialis.…”
mentioning
confidence: 99%
“…Therefore, 2 to 36% of nucleoside analogue usage may have been for oral or labial HSV-1; if one can extrapolate from the prescriptions that did specify the site of infection, then the actual percentage used for RHL is near the low end of this interval. In calculating the figures in scenario 1 for Table 2, we used data on the reduction of HSV-1 shedding in treated patients from efficacy trials to calculate the effect of the fraction of treatment that is directed against herpes labialis or gingivostomatitis (2,52,53). We assumed that the use of these compounds to treat other conditions would affect HSV-1 shedding as if the recipients were taking the drug to suppress RHL (44,51,57).…”
Section: Methodsmentioning
confidence: 99%
“…There are two approaches to the therapy of RHL: episodic treatment of a single symptomatic outbreak, which reduces the duration of symptoms and viral shedding (2,50,52,53), and long-term suppressive therapy, which reduces the frequency of recurrences (44,51). Although neither ACV nor PCV is approved for long-term suppression of RHL, topical PCV has been approved in the United States for treatment of RHL, and in other countries topical ACV and topical PCV are available.…”
mentioning
confidence: 99%